2009
DOI: 10.1093/eurheartj/ehp194
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for pacemaker or implantable cardiac defibrillator implants in patients with high risk of thrombo-embolic events: oral anticoagulation or bridging with intravenous heparin? A prospective randomized trial

Abstract: AimsCurrent guidelines recommend stopping oral anticoagulation (OAC) and starting heparin infusion before implanting/replacing a pacemaker/implantable cardioverter-defibrillator (ICD) in patients with high risk for thrombo-embolic events. The aim of this study was to demonstrate that the maintenance of OAC during device implantation/replacement is as safe as bridging to intravenous heparin and shortens in-hospital stay.Methods and resultsA cohort of 101 consecutive patients with high risk for embolic events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 14 publications
5
70
0
1
Order By: Relevance
“…Amongst higher risk patients with mechanical prosthetic valves, the risk difference for thromboembolic events (between patients continuing and patients discontinuing therapeutic anticoagulation) for seven days was recently estimated to be 0.13-0.29% [17,18]. In the first prospective randomised trial in high risk patients, Tolosana et al [19] recently demonstrated maintenance oral anticoagulation (INR 2.0 ± 0.3) during device implantation is as safe as bridging anticoagulation, achieving a significant mean reduction in length of hospital stay of 2.5 ± 0.7 days.…”
Section: Pacemaker Insertion Is a Common Lifesaving Procedures With mentioning
confidence: 99%
“…Amongst higher risk patients with mechanical prosthetic valves, the risk difference for thromboembolic events (between patients continuing and patients discontinuing therapeutic anticoagulation) for seven days was recently estimated to be 0.13-0.29% [17,18]. In the first prospective randomised trial in high risk patients, Tolosana et al [19] recently demonstrated maintenance oral anticoagulation (INR 2.0 ± 0.3) during device implantation is as safe as bridging anticoagulation, achieving a significant mean reduction in length of hospital stay of 2.5 ± 0.7 days.…”
Section: Pacemaker Insertion Is a Common Lifesaving Procedures With mentioning
confidence: 99%
“…Unfortunately, no randomized data demonstrating that warfarin continuation is superior to warfarin discontinuation exist. 14 …”
Section: Introductionmentioning
confidence: 99%
“…A large randomized controlled trial to compare the 2 strategies (heparin bridging vs. continuation of oral anticoagulation), in patients undergoing pacemaker or ICD implantation is now under way in North America. 37 In the present study, discontinuation of warfarin was made typically 1-2 days prior to operation, thereby maintaining some anticoagulant effects (INR 1.4±0.3, n=29; which was lower than that in the prospective randomized trial by Tolosana et al: 31 INR, 2.0±0.3, n=50). In the Tolosana et al study, the rate of bleeding complication was not different between the 2 perioperative strategies, maintenance of oral anticoagulation and heparin bridging.…”
Section: Resultsmentioning
confidence: 54%
“…31, 36 In contrast to the retrospective studies, 14-16,32-35 a prospective study showed that development of pocket hematoma after implanting/replacing a pacemaker or ICD was observed in 7.8% of patients treated with heparin bridging, and in 8.0% of those with oral anticoagulation who maintained an INR of 2±0.3. 31 In another prospective study, there was a trend toward reduced complications in patients with warfarin continuation, 36 but the results were not statistically significant, possibly due to the small number of patients (n=7) randomized to heparin bridging. A large randomized controlled trial to compare the 2 strategies (heparin bridging vs. continuation of oral anticoagulation), in patients undergoing pacemaker or ICD implantation is now under way in North America.…”
Section: Resultsmentioning
confidence: 97%